Analysis of Leading Plantation Commodities Using The AHP (Analitycal Hierarchy Process) Method in West Muna District - Muhammad Fadholl Ichsan; La Rianda; Sukmawati Abdullah (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
This study aims to analyze superior plantation commodities using the AHP (Analytical Hierarchy Process) method in West Muna Regency. This research was conducted from October to December 2022 on superior plantation commodities in West Muna Regency. Data collection was carried out using interviews, questionnaires, and documentation. The results showed that the priority criteria for superior plantations in the development of superior plantation commodities in West Muna Regency included land suitability (KL) of 0.076, market orientation (OP) of 0.152, added value (NT) of 0.022, local government policy (KPD) of 0.118, environmentally friendly (RL) of 0.036, contribution to community income (KTPM) of 0.222, and feasibility for business development (LBPB) of 0.304. The leading plantation commodities in West Muna Regency had the highest weights, showing coconut (0.466), cashew (0.282), and cocoa (0.251).